2009
DOI: 10.1016/j.rgg.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Lower–Middle Jurassic foraminiferal and ostracode biostratigraphy of the Barents Sea shelf

Abstract: The Barents Sea shelf is an attractive target as a prospective large petroleum province. Further development of geological and geophysical exploration in the area requires high-resolution biostratigraphic constraints and update stratigraphic charts. The zonal succession of Lower and Middle Jurassic assemblages of foraminifers and ostracodes of the Barents Sea fits well the division for northern Siberia based on correlated independent Jurassic and Cretaceous zonal scales on all main microfossil groups, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The first hypothesis takes into account a Middle Jurassic production of nannofossils restricted to the shallow seas of the continental shelf (Hay, 2004), which were located in between 60°N and 60°S. We selected this latitude range because sections from Siberia and Alaska located north of 60°N, and Canada and Scotland located slightly below 60°N during the Middle Jurassic do not contain limestone or marlstone deposits (Imlay, 1976;Morton, 1992;Hall et al, 2004;Basov et al, 2009). Following this hypothesis, S would correspond to~6% of the Earth's surface during this period (measured from Blakey, 2005).…”
Section: Carbon Fluxes From Nannofossils Extrapolated At the World-scalementioning
confidence: 99%
“…The first hypothesis takes into account a Middle Jurassic production of nannofossils restricted to the shallow seas of the continental shelf (Hay, 2004), which were located in between 60°N and 60°S. We selected this latitude range because sections from Siberia and Alaska located north of 60°N, and Canada and Scotland located slightly below 60°N during the Middle Jurassic do not contain limestone or marlstone deposits (Imlay, 1976;Morton, 1992;Hall et al, 2004;Basov et al, 2009). Following this hypothesis, S would correspond to~6% of the Earth's surface during this period (measured from Blakey, 2005).…”
Section: Carbon Fluxes From Nannofossils Extrapolated At the World-scalementioning
confidence: 99%
“…A succession of four biostratigraphic units (Fig. 10) also defined in all other Arctic regions (Azbel' et al, 1991;Basov et al, 1989Basov et al, , 2008 was identified in Albian sediments of northern and northwestern areas of West Siberia (Nesterov, 1991).…”
Section: Zonal Scales For Benthic Groups (Bivalves Foraminifers Ostmentioning
confidence: 78%
“…Some biostratigraphic units (KF1, KF2, KF4, KF5) are defined in all Arctic regions: West Siberia, East Siberia, Arctic Alaska, Arctic Canada, and Barents Sea shelf (Basov et al, 2008;Fowler and Braun, 1993;Shurygin et al, 2000;Wall, 1983). Since the second half of the Hauterivian, a predominantly continental regime had set in East Siberia (Fig.…”
Section: Zonal Scales For Benthic Groups (Bivalves Foraminifers Ostmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of the black shale facies here can be roughly estimated as Kimmeridgian-Ryazanian. TOC values of these black shales lie mainly between 2 and 23%, but fluctuations of TOC distribution through the succession remains unclear (Basov et al 2009). Fossils recovered from these black shales mainly belong to ammonites and Buchia; in addition to these groups, lingulid brachiopods, coleoid hooks and onychites (including big-sized megaonychites) were reported from the Volgian interval of black shales.…”
mentioning
confidence: 98%